2021
DOI: 10.1002/star.202100213
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Structure, and Properties of Enzymatically‐Hydrolyzed Starch for Slowing Down the Retrogradation of High Starchy Foods

Abstract: Amylase represents a green and healthy method that can be used to inhibit retrogradation of starch and high starchy foods. In this study, glutinous rice starch is hydrolyzed using α‐amylase or β‐amylase at different dextrose equivalent (DE) values to investigate the effect of enzymatically‐hydrolyzed glutinous rice starch (EGS) on the anti‐retrogradation of rice cakes. The latter's hardness shows that EGS successfully slowed down the retrogradation of rice cakes with this effect being dependent on the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Primarily consumed as a staple food, rice is also processed to yield an array of convenient and expedient snack products with diverse flavors and styles [4]. Given that starch constitutes approximately 70% of the composition of rice, the staling phenomenon occurs unavoidably during processes such as transportation, storage, and sale, causing alterations in its intrinsic attributes, including decreased solubility in water, diminished palatability, and impaired digestive properties [5]. Freshly baked bread exhibits a desirable texture, is soft yet resilient in structure, and is elastic [6].…”
Section: Introductionmentioning
confidence: 99%
“…Primarily consumed as a staple food, rice is also processed to yield an array of convenient and expedient snack products with diverse flavors and styles [4]. Given that starch constitutes approximately 70% of the composition of rice, the staling phenomenon occurs unavoidably during processes such as transportation, storage, and sale, causing alterations in its intrinsic attributes, including decreased solubility in water, diminished palatability, and impaired digestive properties [5]. Freshly baked bread exhibits a desirable texture, is soft yet resilient in structure, and is elastic [6].…”
Section: Introductionmentioning
confidence: 99%
“…These hydrolases have been successful in modification of starch to impart thickening and gelling effects as a stabilizer, as well as in preparation of porous structure and retardation of retrogradation. [4,6] Recently, it was reported that maltogenic 𝛼-amylase could act on the starch granule to create visible pores, improve retrogradation behavior, and reduce digestibility. [7,8] Moreover, the maltohexaose-forming 𝛼amylase, another member of maltooligosaccharide-forming amylases, could efficiently hydrolyze the raw starch granule into a porous structure at subgelatinization temperature.…”
Section: Introductionmentioning
confidence: 99%